Optimal Tunnel Positioning and Graft Diameter to Minimize Impingement in Single-Bundle ACL Reconstruction: A 3D CT Simulation Analysis - Sang-Woo Jeon; Sung-Hwan Kim; Kang-Il Kim (Medicina, 2025)
Background and Objectives: Graft impingement against the intercondylar notch has been identified as a significant contributor to graft deterioration and suboptimal outcomes following anterior cruciate ligament (ACL) reconstruction. This study aimed to (1) identify the optimal combination of tunnel positions that minimizes impingement between the ACL graft and femoral intercondylar notch. Materials and Methods: Three-dimensional models of nine normal knees were reconstructed using computed tomography scans obtained at four knee flexion angles (0°, 45°, 90°, and 120°). Virtual ACL grafts with diameters of 7 mm and 9 mm were modeled as cylinders. Nine graft configurations were investigated by varying femoral and tibial footprint locations (anteromedial, central, and posterolateral) in all possible combinations. For each configuration, impingement volume was quantified by measuring the overlap between the intercondylar notch and the virtual graft using Boolean operators in 3D simulation software. The effects of graft diameter, footprint location, and knee flexion angle on impingement volume were analyzed. Results: Maximum impingement volumes were observed at 0° knee extension, with significant reductions at 45° flexion (p < 0.01) and negligible impingement at 90° and 120° flexion. The 9 mm diameter grafts demonstrated significantly greater impingement volumes than 7 mm grafts (p < 0.01). Impingement volumes increased progressively as footprint locations shifted from posterolateral to anteromedial positions in both femoral and tibial components. However, statistically significant differences in impingement volume across footprint locations were observed only for tibial positioning (p < 0.001), not for femoral positioning (p > 0.05). The femoral anteromedial-tibial anteromedial configuration exhibited the highest impingement volume (577.8 ± 171.3 mm3 for 9 mm grafts), while the femoral posterolateral-tibial posterolateral configuration showed the lowest (73.5 ± 85.6 mm3). Conclusions: Tunnel position, graft diameter, and knee flexion angle significantly influence impingement risk in ACL reconstruction. Tibial tunnel position appears more critical than femoral position in minimizing graft impingement. Posterolateral positioning of tunnels, particularly on the tibial side, may reduce impingement volume. Clinical Relevance: This study provides quantitative evidence to guide surgeons in optimizing tunnel placement and graft selection for anatomical single-bundle ACL reconstruction, potentially reducing the risk of graft deterioration and failure due to mechanical impingement.